Indicators of carbohydrate metabolism in a patient with dyslipidemia and impaired fasting glycemia receiving pitavastatin: a case report - A. A. Nekrasov; E. S. Timoshchenko; D. V. Cherneva; I. N. Volovatova; T. A. Nekrasova (Кардиоваскулярная терапия и профилактика, 2023)
Statins have diabetogenic properties. Pitavastatin is currently considered the only drug in this group that combines high lipid-correcting activity with the absence of a negative effect on carbohydrate metabolism. The article presents a case of correction of carbohydrate metabolism indicators against the background of pitavastatin therapy in a patient with dyslipidemia and impaired fasting glycemia. The optimal algorithms for the examination and treatment of such patients are discussed on the example of this patient.